(untitled) (International Journal of Engineering and Computer Science, 2014)
This paper discuses the attempt done to provide secret communication technique by hiding confidential data in image. Here steganography along with cryptography is used to strengthen the security. Steganography hides existence of data while cryptography protects the information by transforming it into an encrypted form. Asymmetric key cryptography technique – RSA is used to encrypt the secret data and then Haar- DWT transformation algorithm is used to embed the secret data which is in encrypted form. Experimental result shows image quality parameters like PSNR and Mean Absolute Error.